Correlates of night‐time and exercise‐associated lower limb cramps in healthy adults. Issue 3 (5th July 2021) - Hawke, Fiona; McKay, Marnee J.; Baldwin, Jennifer N.; Chiu, Simon; Sadler, Sean; Oldmeadow, Christopher; Chuter, Vivienne; Burns, Joshua
Abstract: Introduction/Aims: We explored correlates of night‐time and exercise‐associated lower limb cramps in participants of the 1000 Norms Project. Methods: A volunteer community sample of healthy people aged ≥18 y underwent assessment of motor function and physical performance, and were questioned about muscle cramps in the previous 3 mo. Results: Of 491 (221 female) participants age 18–101 y (mean: 59.12; SD: 18.03), about 1 in 3 experienced night‐time lower limb cramps, and about 1 in 4 experienced exercise‐associated lower limb cramps. For night‐cramps, a one unit increase in Beighton score (greater whole‐body flexibility) was associated with a 31% reduced odds of cramps (odds ratio [OR] = 0.69, 95% confidence interval [CI]:0.45, 0.99) and passing all three lesser‐toe strength tests was associated with 50% reduced odds of cramps (OR = 0.50, 95% CI: 0.32, 0.78). For exercise‐associated cramps, participants in the fourth (lowest arch) quartile of Foot Posture Index were 2.1 times (95% CI: 1.11, 3.95) more likely to experience cramps than participants in the first (highest arch) quartile. Odds of experiencing both types of cramps versus no cramps were lower with passing all three lesser‐toe strength tests (OR = 0.40, 95% CI: 0.19, 0.85) and better performance in the six‐minute walk test (OR = 0.997, 95% CI: 0.996, 0.998). Discussion: People who experienced both exercise‐associated and night‐time cramps were less functional. The association between night‐time cramps with less whole‐body flexibility and reduced lesser‐toe flexor strength should be explored to determine causation. Planovalgus (low‐arched) foot type was independently associated with exercise‐associated cramps. The effectiveness of foot orthoses for secondary prevention of exercise‐associated cramps in people with low‐arched feet should be explored.